Severe Hypothyroidism Causing Pre-Eclampsia-Like Syndrome - Annalisa Inversetti; Audrey Serafini; Marco F. Manzoni; Anna Dolcetta Capuzzo; Luca Valsecchi; Massimo Candiani (Case Reports in Endocrinology)
Objective. Analyzing and managing pre-eclampsia-like syndrome due to severe hypothyroidism. Methods. Presentation of a case of severe hypothyroidism due to Hashimoto’s syndrome, associated with a severe early-onset preeclampsia-like syndrome, managed in our Gynecology Department. Results. Severe pre-eclampsia led to miscarriage at 24 weeks of gestational age in a 42-year-old woman, although we attempted to correct hypothyroidism with increasing doses of levothyroxine and liothyronine sodium. Conclusion. Recognizing pre-eclampsia-like syndrome caused by overt hypothyroidism from other forms of pregnancy-induced hypertension is essential for choosing the correct treatment.